Clinical characteristics and MRI features of autoimmune glial fibrillary acidic protein astrocytopathy: a case series of 34 patients - Ke, Gaotan; Jian, Si; Yang, Tingxin; Zhao, Xu (Frontiers in Neurology, 2024)
Objectives To analyze the clinical and imaging characteristics of autoimmune glial fibrillary acidic protein astrocytopathy (GFAP-A). Methods Forty-three patients diagnosed with GFAP-A between March 2017 and July 2023 were retrospectively recruited. The clinical characteristics and magnetic resonance imaging (MRI) features were collected. Results Twenty-one patients (61.8%) had a fever and 16 (47.1%) had a headache. Five patients (14.7%) had coexisting neural autoantibodies and one patient (2.9%) had a coexisting neoplasm. The most common presentation was meningoencephalomyelitis (13/34, 38.3%), followed by meningoencephalitis (12/34, 35.3%). The other clinical manifestations included blurred visions (5/34, 14.7%) and peripheral nervous system involvement (4/34, 11.8%). Twenty-six patients (76.5%) had elevated nucleated cell count, predominantly lymphocytes (15/15, 100%), and 27 (79.4%) had elevated protein levels of cerebrospinal fluid. One-half (50%) of the patients presented with hyponatremia. A majority of the patients (30/33, 90.9%) exhibited abnormal hyperintense lesions on T2WI, which were often located in juxtacortical white matter (18/33, 54.5%), followed by periventricular white matter (16/33, 48.5%), basal ganglia (15/ 33, 45.5%), brainstem (11/33, 33.3%), and thalamic lesions (9/33, 27.3%). Twenty-four patients (72.7%) had abnormal brain enhancement, with supratentorial leptomeningeal enhancement being the most frequent enhancement pattern (15/33, 45.5%), followed by linear perivascular radial enhancement (14/33, 42.4%). Nineteen patients (70.4%) had hyperintense intramedullary spinal cord lesions, with long segments (15/27, 55.6%) and transverse lesions (14/27, 51.9%) being the most frequent lesions. Most cases were sensitive to immunotherapy, such as glucocorticoids, intravenous immunoglobulin, and tacrolimus, with three patients (8.8%) experiencing relapses. Patients with brainstem lesions had higher onset modified Rankin scale scores and were more prone to intensive care unit admissions. Linear perivascular radial enhancement was positively associated with poor prognosis (p < 0.05). Conclusion GFAP-A presented with meningoencephalomyelitis and meningoencephalitis. The brain lesions were often located in juxtacortical white matter, periventricular white matter, basal ganglia, brainstem, and thalamus. Long segments and transverse were the most frequent spine lesions. Leptomeningeal enhancement was the most frequent enhancement pattern, followed by linear perivascular radial enhancement, which may provide new insight into the differential diagnosis of GFAP-A.